Empowering Smes Through Digital Marketing At Unesco Global Geopark Belitong, Indonesia - Ayu Krishna Yuliawati; Rofi Rofaida; Budhi Pamungkas (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2021)
During the COVID-19 pandemic, SMEs located in tourism destinations in the form of small islands in Indonesia experienced many problems, including: decreased sales turnover due to reduced number of tourists coming to visit the island, difficulty in raw materials, rising raw material prices and SMEs not understanding how to do digital marketing effectively. Digital skills for SMEs are very important in building a competitive advantage and expanding the market not only in their area. Therefore, a community empower program was initiated to help the SMEs survive through covid19 pandemic, by increasing their capacity on Digital Marketing.The objectives of this program are:(1) to develop community empowerment through Digital Marketing program (2) to increase community skills in digital marketing. Eight months of educational activities were conducted on 20 SMEs from April 2021 to November 2021 at the Unesco Global Geopark Belitong. Using the parcipatory training method, SMEs were able to understand how to conduct digital marketing. The result of this program, is SMEs start to develop their own digital marketing program, with the help from university students. For future program SMEs express their hope that coaching and upskilling in digital marketing will continue in order to help them increase their market.